Directing innovation towards just outcomes: the role of principles and politics - Theo Papaioannou (Journal of Responsible Innovation)
Contemporary innovation theorists tend to defend a combination of Schumpeterian and Keynesian politics of innovation as a solution to the problem of the directionality of new technologies. Their hope is that the Schumpeterian motor of innovation would keep entrepreneurs incentivised to take market opportunities and the Keynesian state would invest in infrastructure, redistributing risks and rewards. In contrast, Hayekian theorists of innovation insist that state interventions aiming at directionality suffer from epistemological and moral problems. For them, politics of innovation ought to abandon the idea of directionality altogether because it is morally questionable and creates disincentives for taking up new risky ventures. Instead, the politics of innovation ought to be restricted to promoting an institutional environment that is conducive to entrepreneurship. I will argue that despite differences, both theoretical camps rely on liberal notions of morality and politics which justify predominantly distributional currencies of justice, overlooking questions of relational equality in innovation.